High-performance corrosion-resistant nickel-based alloy plate and preparation method thereof

By using plasma activation of nano-zirconia particles and passivation treatment with a composite acid system, combined with precision rolling technology, a stable interface layer and a longitudinal layered carbide structure are formed, which solves the problem of uneven corrosion resistance of nickel-based alloy plates and improves their comprehensive corrosion protection capability under high temperature and high pressure environments.

CN121380684APending Publication Date: 2026-01-23上海一郎合金材料有限公司
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202511658934.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-13
Publication Date
2026-01-23

AI Technical Summary

Technical Problem

The passivation film formation ability of different regions of nickel-based alloy plates varies under high-temperature corrosion environments, making it difficult to guarantee the non-uniformity of corrosion resistance.

Method used

Plasma activation treatment with nano-zirconia particles of specific composition is used, combined with passivation treatment with a composite acid system and precision rolling process to form a γ-Ni matrix phase and a longitudinal layered carbide structure, in which nano-titanium dioxide particles are embedded, and the corrosion resistance is improved through chemical bonding and directional barrier.

Benefits of technology

It achieves resistance to uniform corrosion and stress corrosion cracking in nickel-based alloy plates under high temperature and high pressure environments, and has excellent resistance to pitting corrosion and fouling, making it suitable for long-term protection under extreme working conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121380684A_ABST
    Figure CN121380684A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of alloy processing, and discloses a high-performance corrosion-resistant nickel-based alloy plate and a preparation method thereof, and the method comprises the following steps: raw material preparation, smelting treatment, casting treatment, hot rolling treatment, solution treatment, aging treatment and surface passivation treatment. According to the invention, when a composite acid system is adopted for passivation treatment, the concentration of chromium / molybdenum atoms in a passivation film is optimized and balanced due to the specific ratio of nitric acid to chromic acid, a chromium oxide provides a compact passivation barrier, and a molybdenum oxide endows the film layer with a self-repairing characteristic to synergistically inhibit pitting nucleation; meanwhile, nano titanium dioxide particles pretreated by silane are embedded into the passivation film in situ under the action of ultrasonic oscillation, organic pollutants adsorbed on a film layer can be decomposed by the photocatalytic characteristic of the nano titanium dioxide particles, the local corrosion effect of a battery caused by dirt coverage is avoided, and the performance of the battery is improved through double upgrading of components and the structure of the passivation film. And the alloy plate has excellent pitting corrosion resistance and fouling resistance in a chloride ion-containing medium.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of alloy processing technology, specifically to a high-performance corrosion-resistant nickel-based alloy sheet and its preparation method. Background Technology

[0002] Nickel-based alloys are a class of alloys that possess high strength at high temperatures and a certain degree of resistance to oxidation and corrosion. With high room temperature and high temperature strength, as well as good oxidation and corrosion resistance, nickel-based alloys are widely used in the petrochemical, energy, machinery, and environmental protection industries, making them an indispensable and extremely important material for economic development and national defense.

[0003] Currently, due to the coupling of multiple processes in the preparation of nickel-based alloy plates, conventional process methods are difficult to suppress the micro-segregation of alloying elements during the smelting stage when controlling the corrosion resistance of alloys in high-temperature corrosion environments. When local component concentration fluctuations occur inside the melt, the passivation film formation ability in different areas of the plate will vary, and the uniformity of corrosion resistance cannot be guaranteed.

[0004] Therefore, a high-performance corrosion-resistant nickel-based alloy plate and its preparation method are proposed to solve the above problems. Summary of the Invention

[0005] To address the shortcomings of existing technologies, this invention provides a high-performance corrosion-resistant nickel-based alloy plate and its preparation method, solving the problem mentioned in the background art where the passivation film formation ability varies in different regions of the plate, making it impossible to guarantee the uniformity of corrosion resistance.

[0006] To achieve the above objectives, the present invention provides the following technical solution: a high-performance corrosion-resistant nickel-based alloy plate and its preparation method, wherein the plate is composed of the following components by weight percentage: Nickel: 55-65%, Chromium: 18-22%, Molybdenum: 8-12%, Iron: 2-5%, Niobium: 1-3%, Carbon: 0.05-0.15%, Yttrium: 0.05-0.2%, Nano-zirconia particles: 0.1-0.5%, the remainder being unavoidable impurities, including sulfur ≤0.01%, phosphorus ≤0.02%, oxygen ≤0.005%, and the total amount of impurities ≤0.5%; The nano-zirconia particles have a particle size of 30-80 nanometers and their surfaces are plasma-activated, resulting in a hydroxyl density of 5-8 hydroxyl groups per square nanometer on the particle surface. The microstructure of the alloy plate consists of a γ-Ni matrix phase and a dispersed C carbide composite phase. The average size of the carbides in the C carbide composite phase is ≤500 nanometers, and they are distributed in a longitudinal layered manner with an interlayer spacing of 0.5-1.5 micrometers. The plate surface is covered with a passivation film with a thickness of 50-200 nanometers and a chromium / molybdenum atomic concentration ratio of 2.0-3.5. Titanium dioxide particles with a particle size of 20-50 nanometers are also embedded in the film.

[0007] Preferably, the method includes the following steps: Step 1: Raw material preparation, weigh the raw materials according to the stated ingredient ratio; Step 2: Melting process, place the raw materials in a vacuum induction furnace and melt them under an inert atmosphere; Step 3: Casting process, pouring the molten metal into slabs; Step 4: Hot rolling treatment, the slab is heated and then rolled into shape; Step 5: Solution treatment, the rolled sheet is subjected to high-temperature solution treatment; Step Six: Aging Treatment, subjecting the solution-treated board to medium-temperature aging; Step 7: Surface passivation treatment. Immerse the aged plate in passivation solution.

[0008] Preferably, in step one, the plasma activation treatment of the nano-zirconia particles includes: placing the particles in a vacuum of 1× Up to 1× In a reaction chamber at Pa, argon flow rate of 20-50 sccm and plasma power of 400-600 W, the plasma was processed for 10-20 minutes.

[0009] Preferably, in step two, the melting is carried out under an argon atmosphere at a temperature of 1550-1600℃, held for 1.5-2 hours, and with a vacuum degree ≤1× Pa, and use an electromagnetic stirrer to continuously stir at 50-100 r / min.

[0010] Preferably, in step three, the casting process includes: pouring molten metal into a copper mold preheated to 800-900℃, coating the surface with a 0.1-0.3mm boron nitride coating to prevent the molten metal from sticking together and to regulate the cooling rate; the pouring speed is 10-20cm. 3 After casting, the slab is cooled to room temperature by water at a rate of 5-10℃ / s to obtain a 50-100mm thick slab.

[0011] Preferably, the hot rolling process in step four includes: The slab is held at 1100-1200℃ for 1-2 hours, and then rolled on a four-roll hot rolling mill at a pressure of 15-20MPa and a speed of 0.5-1.5m / s with a total reduction of 70-80% to obtain a longitudinal layered carbide structure with an interlayer spacing of 0.5-1.5 micrometers. Each pass requires a reduction of ≤20%, and a water mist cooling system is used to control the board temperature at 900-1000℃.

[0012] Preferably, the solution treatment in step five involves a nitrogen-hydrogen mixed gas volume ratio of... : The mixture is prepared in a 95:5 ratio at a temperature of 1020-1080℃, and after holding at that temperature for 1-2 hours, it is quenched in water at a rate of ≥50℃ / s to 20-30℃ in deionized water.

[0013] Preferably, the aging treatment in step six includes: holding at 700-750℃ for 4-8 hours, followed by forced air cooling at a wind speed of 5-10m / s. Before the aging treatment, the surface of the board is coated with an anti-oxidation coating, which is composed of silica sol and alumina powder in a mass ratio of 1:1, and the coating thickness is 10-20 micrometers.

[0014] Preferably, the surface passivation treatment in step seven includes: The plate is immersed in a passivation solution at 40-60℃ for 30-60 minutes. The passivation solution consists of nitric acid, chromic acid and corrosion inhibitor, with a mass ratio of nitric acid:chromic acid:corrosion inhibitor = 5:3:1. The concentration of nitric acid is 40-50wt%, the concentration of chromic acid is 20-30wt%, and benzotriazole is used as the corrosion inhibitor to achieve a Cr / Mo atomic ratio of 2.0-3.5 in the passivation film. During immersion, the ultrasonic oscillator is activated every 10-15 minutes at a frequency of 20-40 kHz and a power density of 0.5-1.0 W / cm³. 2 The oscillation time is 3-5 minutes.

[0015] Preferably, the passivation solution further contains nano-titanium dioxide particles with a particle size of 20-50 nm and a total mass of 0.1-0.3%. The particles are pretreated with silane coupling agent KH-550: the particles are dispersed in ethanol, 2-5 wt% KH-550 is added, and the mixture is stirred at 60°C for 2 hours and then centrifuged and dried to allow the titanium dioxide to be uniformly embedded in the passivation film.

[0016] Compared with the prior art, the present invention provides a high-performance corrosion-resistant nickel-based alloy plate and its preparation method, which has the following beneficial effects: 1. In this invention, plasma activation of nano-zirconia particles results in a high-density hydroxyl group on their surface. This highly active surface improves the wettability of the melt to the particles in the early stages of smelting and acts as an active site, inducing interfacial chemical reactions between the particles and the matrix alloying elements. Ultimately, a stable transitional interface layer bonded by chemical bonds is formed between the two, achieving a strong and tough bond between the particles and the matrix. This blocks the diffusion channels of corrosive media along the particle-matrix interface. At the same time, the rare earth element yttrium preferentially accumulates at the grain boundaries, inhibiting the precipitation of chromium carbides at the grain boundaries and improving the intergranular corrosion resistance of the alloy in a strong acid environment. The longitudinally layered carbide structure is formed by a precision rolling process, constructing a directional barrier parallel to the surface of the plate during corrosion, slowing down the rate of corrosion penetration, and achieving long-term protective stability of the alloy plate under extreme working conditions.

[0017] 2. In this invention, when a composite acid system is used for passivation treatment, the specific ratio of nitric acid to chromic acid promotes an optimized balance of chromium / molybdenum atom concentration in the passivation film. Chromium oxide provides a dense passivation barrier, while molybdenum oxide imparts self-healing properties to the film layer, synergistically inhibiting pitting nucleation. Simultaneously, nano-titanium dioxide particles pretreated with silane are in situ embedded in the passivation film under ultrasonic oscillation. Their photocatalytic properties can decompose organic pollutants adsorbed on the film layer, avoiding the localized corrosion cell effect caused by dirt coverage. Through the dual upgrade of passivation film composition and structure, the alloy plate has excellent anti-pitting corrosion and anti-fouling capabilities in chloride ion-containing media.

[0018] 3. In this invention, the solution treatment stage employs a nitrogen-hydrogen mixed atmosphere protection combined with water quenching. Hydrogen atoms penetrate the alloy lattice at high temperature to inhibit carbide coarsening. Subsequently, rapid cooling locks in the metastable supersaturated solid solution, laying the foundation for subsequent aging to control carbide size. In the aging process, forced air cooling combined with a surface anti-oxidation coating ensures uniform precipitation of carbides within a specific temperature range, eliminating the tendency of micro-area galvanic corrosion caused by local stress concentration. Through full-process microstructure control, the alloy plate is ultimately endowed with comprehensive resistance to uniform corrosion and stress corrosion cracking in high-temperature and high-pressure environments. Attached Figure Description

[0019] Figure 1 This is a flowchart illustrating a high-performance corrosion-resistant nickel-based alloy plate and its preparation method according to the present invention. Detailed Implementation

[0020] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0021] Example 1: A high-performance corrosion-resistant nickel-based alloy plate and its preparation method, wherein the plate is composed of the following components by weight percentage: Nickel: 57.3%, Chromium: 22%, Molybdenum: 12%, Iron: 5%, Niobium: 3%, Carbon: 0.05%, Yttrium: 0.05%, Nano-zirconia particles: 0.1%, the remainder being unavoidable impurities, including sulfur ≤0.01%, phosphorus ≤0.02%, oxygen ≤0.005%, and the total amount of impurities ≤0.5%; The nano-zirconia particles have a particle size of 30 nanometers and their surfaces are plasma-activated, resulting in a hydroxyl density of 5 hydroxyl particles per square nanometer on the particle surface after activation. The microstructure of the alloy plate consists of a γ-Ni matrix phase and a dispersed (Nb,Mo)C carbide composite phase. The average size of the carbides in the C carbide composite phase is ≤500 nanometers, and they are distributed in a longitudinal layered manner with an interlayer spacing of 0.5 micrometers. The plate surface is covered with a passivation film with a thickness of 50 nanometers and a chromium / molybdenum atomic concentration ratio of 2.0. It also contains titanium dioxide particles with a particle size of 20 nanometers.

[0022] The method includes the following steps: Step 1: Raw material preparation, weigh the raw materials according to the ingredient ratio; Step 2: Melting process, place the raw materials in a vacuum induction furnace and melt them under an inert atmosphere; Step 3: Casting process, pouring the molten metal into slabs; Step 4: Hot rolling treatment, the slab is heated and then rolled into shape; Step 5: Solution treatment, the rolled sheet is subjected to high-temperature solution treatment; Step Six: Aging Treatment, subjecting the solution-treated board to medium-temperature aging; Step 7: Surface passivation treatment. Immerse the aged plate in passivation solution.

[0023] In step one, the plasma activation treatment of the nano-zirconia particles includes: placing the particles in a vacuum of 1× The reaction chamber was treated for 10 minutes at an argon flow rate of 20 sccm and a plasma power of 400 W.

[0024] In step two, the melting is carried out under an argon atmosphere at a temperature of 1550℃ for 1.5 hours, with a vacuum degree ≤1× Pa, and continuously stirred at 50 r / min using an electromagnetic stirrer.

[0025] Step three, the casting process includes: pouring molten metal into a copper mold preheated to 800°C, coating the surface with a 0.1mm boron nitride coating to prevent the molten metal from sticking together and to regulate the cooling rate; the pouring speed is 10cm. 3After casting, the slab is cooled to room temperature at a rate of 5℃ / s to obtain a 50mm thick slab.

[0026] Step four, the hot rolling process, includes: The slab was held at 1100℃ for 1 hour, and then rolled on a four-roll hot rolling mill at a pressure of 15MPa and a speed of 0.5m / s with a total reduction of 70% to obtain a longitudinal layered carbide structure with an interlayer spacing of 0.5 micrometers. Each pass requires a reduction of ≤20%, and the board temperature is controlled at 900℃ using a water mist cooling system.

[0027] Step five, the solution treatment, involves a nitrogen-hydrogen mixed gas volume ratio of... : The mixture was prepared in a 95:5 ratio at 1020℃, and after holding at that temperature for 1 hour, it was quenched in water at a rate of ≥50℃ / s to 20℃ in deionized water.

[0028] Step six, the aging treatment, includes: holding at 700℃ for 4 hours, followed by forced air cooling at a wind speed of 5m / s. Before the aging treatment, the surface of the board is coated with an anti-oxidation coating for protection. The coating consists of silica sol and alumina powder in a 1:1 mass ratio and has a thickness of 10 micrometers. This prevents surface oxidation and stress corrosion during the aging treatment and ensures uniform precipitation of carbides. After the aging treatment, the surface coating is removed by mechanical grinding to provide a clean and active surface for passivation treatment.

[0029] Step seven, surface passivation treatment, includes: The plate was immersed in a passivation solution at 40°C for 30 minutes. The passivation solution consisted of nitric acid, chromic acid and corrosion inhibitor. The mass ratio of each component was nitric acid: chromic acid: corrosion inhibitor = 5:3:1. The concentration of nitric acid was 40wt%, the concentration of chromic acid was 20wt%, and benzotriazole was used as the corrosion inhibitor to make the Cr / Mo atomic ratio of the passivation film reach 2.0. During the immersion process, an ultrasonic oscillator was activated every 10 minutes at a frequency of 20 kHz and a power density of 0.5 W / cm³. 2 The oscillation time is 3 minutes.

[0030] The passivation solution also contains nano-titanium dioxide particles with a particle size of 20 nm and a total mass of 0.1%. The particles are pretreated with silane coupling agent KH-550: the particles are dispersed in ethanol, 2 wt% KH-550 is added, and the mixture is stirred at 60°C for 2 hours and then centrifuged and dried to allow the titanium dioxide to be uniformly embedded in the passivation film.

[0031] The plasma activation treatment was carried out in an RF plasma device with the following parameters: the working gas was high-purity argon, the gas flow rate was 50 sccm, the chamber vacuum was 10 Pa, the RF power was 150 W, and the treatment time was 15 minutes.

[0032] Example 1: Control Experiment on the Effect of Plasma Activation Power

[0033] Example 2: A high-performance corrosion-resistant nickel-based alloy plate and its preparation method, wherein the plate is composed of the following components by weight percentage: Nickel: 63%, Chromium: 20%, Molybdenum: 10%, Iron: 4%, Niobium: 2%, Carbon: 0.1%, Yttrium: 0.15%, Nano-zirconia particles: 0.25%, the remainder being unavoidable impurities, including sulfur ≤0.01%, phosphorus ≤0.02%, oxygen ≤0.005%, and the total amount of impurities ≤0.5%; The nano-zirconia particles have a particle size of 50 nanometers and their surfaces are plasma-activated, resulting in a hydroxyl density of 6 hydroxyl particles per square nanometer. The microstructure of the alloy plate consists of a γ-Ni matrix phase and a dispersed (Nb,Mo)C carbide composite phase. The average size of the carbides in the C carbide composite phase is ≤500 nanometers, and they are distributed in a longitudinal layered manner with an interlayer spacing of 1.0 micrometers. The plate surface is covered with a passivation film with a thickness of 100 nanometers and a chromium / molybdenum atomic concentration ratio of 3.0. It also contains titanium dioxide particles with a particle size of 30 nanometers.

[0034] The method includes the following steps: Step 1: Raw material preparation, weigh the raw materials according to the ingredient ratio; Step 2: Melting process, place the raw materials in a vacuum induction furnace and melt them under an inert atmosphere; Step 3: Casting process, pouring the molten metal into slabs; Step 4: Hot rolling treatment, the slab is heated and then rolled into shape; Step 5: Solution treatment, the rolled sheet is subjected to high-temperature solution treatment; Step Six: Aging Treatment, subjecting the solution-treated board to medium-temperature aging; Step 7: Surface passivation treatment. Immerse the aged plate in passivation solution.

[0035] In step one, the plasma activation treatment of the nano-zirconia particles includes: placing the particles in a vacuum of 1× The reaction chamber was treated for 15 minutes at an argon flow rate of 35 sccm and a plasma power of 500 W.

[0036] In step two, the melting is carried out under an argon atmosphere at a temperature of 1580℃, held for 1.8 hours, and with a vacuum degree ≤1× Pa, and continuously stirred at 70 r / min using an electromagnetic stirrer.

[0037] Step three, the casting process includes: pouring molten metal into a copper mold preheated to 850°C, coating the surface with a 0.2mm boron nitride coating to prevent the molten metal from sticking together and to regulate the cooling rate; the pouring speed is 15cm. 3 After casting, the slab is cooled to room temperature at a rate of 8℃ / s to obtain a 70mm thick slab.

[0038] Step four, the hot rolling process, includes: The slab was held at 1150℃ for 1.5 hours and then rolled on a four-roll hot rolling mill at a pressure of 18MPa and a speed of 1.0m / s with a total reduction of 75% to obtain a longitudinal layered carbide structure with an interlayer spacing of 1.0 micrometers. Each pass requires a reduction of ≤20%, and the board temperature is controlled at 950℃ using a water mist cooling system.

[0039] Step five, the solution treatment, involves a nitrogen-hydrogen mixed gas volume ratio of... : The mixture was prepared in a 95:5 ratio at 1050℃ and held for 1.5 hours. Then, it was water-quenched at a rate of ≥50℃ / s to 25℃ in deionized water.

[0040] Step six, the aging treatment, includes: holding at 720℃ for 6 hours, followed by forced air cooling at a wind speed of 8m / s. Before the aging treatment, the surface of the board is coated with an anti-oxidation coating for protection. The coating consists of silica sol and alumina powder in a 1:1 mass ratio and has a thickness of 15 micrometers. This prevents surface oxidation and stress corrosion during the aging treatment and ensures uniform precipitation of carbides. After the aging treatment, the surface coating is removed by mechanical grinding to provide a clean and active surface for passivation treatment.

[0041] Step seven, surface passivation, includes: The plate was immersed in a passivation solution at 50°C for 45 minutes. The passivation solution consisted of nitric acid, chromic acid and corrosion inhibitor. The mass ratio of each component was nitric acid: chromic acid: corrosion inhibitor = 5:3:1. The concentration of nitric acid was 45wt%, the concentration of chromic acid was 25wt%, and benzotriazole was used as the corrosion inhibitor to make the Cr / Mo atomic ratio of the passivation film reach 3.0. During the immersion process, an ultrasonic oscillator was activated every 13 minutes at a frequency of 30 kHz and a power density of 0.8 W / cm³. 2 The oscillation time is 4 minutes.

[0042] The passivation solution also contains nano-titanium dioxide particles with a particle size of 30 nm and a total mass of 0.2%. The particles are pretreated with silane coupling agent KH-550: the particles are dispersed in ethanol, 3 wt% KH-550 is added, and the mixture is stirred at 60°C for 2 hours and then centrifuged and dried to allow the titanium dioxide to be uniformly embedded in the passivation film.

[0043] Example 2: Control Experiment on the Effect of Hot Rolling Temperature

[0044] Example 3: A high-performance corrosion-resistant nickel-based alloy plate and its preparation method, wherein the plate is composed of the following components by weight percentage: Nickel: 56.65%, Chromium: 22%, Molybdenum: 12%, Iron: 5%, Niobium: 3%, Carbon: 0.15%, Yttrium: 0.2%, Nano-zirconia particles: 0.5%, the remainder being unavoidable impurities, including sulfur ≤0.01%, phosphorus ≤0.02%, oxygen ≤0.005%, and the total amount of impurities ≤0.5%; The nano-zirconia particles have a particle size of 80 nanometers and their surfaces are plasma-activated, resulting in a hydroxyl density of 8 hydroxyl particles per square nanometer. The microstructure of the alloy plate consists of a γ-Ni matrix phase and a dispersed (Nb,Mo)C carbide composite phase. The average size of the carbides in the C carbide composite phase is ≤500 nanometers, and they are distributed in a longitudinal layered manner with an interlayer spacing of 1.5 micrometers. The plate surface is covered with a passivation film with a thickness of 200 nanometers and a chromium / molybdenum atomic concentration ratio of 3.5. It also contains titanium dioxide particles with a particle size of 50 nanometers.

[0045] The method includes the following steps: Step 1: Raw material preparation, weigh the raw materials according to the ingredient ratio; Step 2: Melting process, place the raw materials in a vacuum induction furnace and melt them under an inert atmosphere; Step 3: Casting process, pouring the molten metal into slabs; Step 4: Hot rolling treatment, the slab is heated and then rolled into shape; Step 5: Solution treatment, the rolled sheet is subjected to high-temperature solution treatment; Step Six: Aging Treatment, subjecting the solution-treated board to medium-temperature aging; Step 7: Surface passivation treatment. Immerse the aged plate in passivation solution.

[0046] In step one, the plasma activation treatment of the nano-zirconia particles includes: placing the particles in a vacuum of 1× The reaction chamber was treated for 20 minutes at an argon flow rate of 50 sccm and a plasma power of 600 W.

[0047] In step two, the melting is carried out under an argon atmosphere at a temperature of 1600℃ for 2 hours, with a vacuum degree ≤1× Pa, and continuously stirred at 100 r / min using an electromagnetic stirrer.

[0048] Step three, the casting process includes: pouring molten metal into a copper mold preheated to 900°C, coating the surface with a 0.3mm boron nitride coating to prevent the molten metal from sticking together and to regulate the cooling rate; the pouring speed is 20cm. 3 After casting, the slab is cooled to room temperature by water at a rate of 10℃ / s to obtain a 100mm thick slab.

[0049] Step four, the hot rolling process, includes: The slab was held at 1200℃ for 2 hours, and then rolled on a four-roll hot rolling mill at a pressure of 20MPa and a speed of 1.5m / s with a total reduction of 80% to obtain a longitudinal layered carbide structure with an interlayer spacing of 1.5 micrometers. Each pass requires a reduction of ≤20%, and the board temperature is controlled at 1000℃ using a water mist cooling system.

[0050] Step five, the solution treatment, involves a nitrogen-hydrogen mixed gas volume ratio of... : The mixture was prepared in a 95:5 ratio at 1080℃ and held for 2 hours. Then, it was quenched in water at a rate of ≥50℃ / s to 30℃ in deionized water.

[0051] Step six, the aging treatment, includes: holding at 750℃ for 8 hours, followed by forced air cooling at a wind speed of 10m / s. Before the aging treatment, the surface of the board is coated with an anti-oxidation coating for protection. The coating consists of silica sol and alumina powder in a 1:1 mass ratio and has a thickness of 20 micrometers. This prevents surface oxidation and stress corrosion during the aging treatment and ensures uniform precipitation of carbides. After the aging treatment, the surface coating is removed by mechanical grinding to provide a clean and active surface for passivation treatment.

[0052] Step seven, surface passivation, includes: The plate was immersed in a passivation solution at 60°C for 60 minutes. The passivation solution consisted of nitric acid, chromic acid and corrosion inhibitor. The mass ratio of each component was nitric acid: chromic acid: corrosion inhibitor = 5:3:1. The concentration of nitric acid was 50wt%, the concentration of chromic acid was 30wt%, and benzotriazole was used as the corrosion inhibitor to make the Cr / Mo atomic ratio of the passivation film reach 3.5. During the immersion process, an ultrasonic oscillator was activated every 15 minutes at a frequency of 40 kHz and a power density of 1.0 W / cm³. 2 The oscillation time is 5 minutes.

[0053] The passivation solution also contains nano-titanium dioxide particles with a particle size of 50 nm and a total mass of 0.3%. The particles are pretreated with silane coupling agent KH-550: the particles are dispersed in ethanol, 5 wt% KH-550 is added, and the mixture is stirred at 60°C for 2 hours and then centrifuged and dried to allow the titanium dioxide to be uniformly embedded in the passivation film.

[0054] Example 3: Control experiment on the effect of passivation solution temperature:

[0055] Comparative Example 1: The difference between this comparative example and Example 1 is that the nano-zirconia particles were not subjected to plasma activation treatment during the preparation of raw materials in this comparative example.

[0056] Comparative Example 2 differs from Example 1 in that: during hot rolling, the rolling parameters were not controlled to obtain a longitudinally layered carbide structure, and the water mist cooling system and interlayer spacing control process were omitted.

[0057] Comparative Example 3 differs from Example 1 in that: in this comparative example, no nano-titanium dioxide particles pretreated with silane were added to the passivation solution during the surface passivation treatment.

[0058] Comparative Example 4 differs from Example 1 in that: during the aging treatment, no silica sol / alumina anti-oxidation coating was applied to the surface of the substrate in this comparative example.

[0059] Comparative Example 5 differs from Example 1 in that yttrium was not added during the preparation of raw materials, i.e., the yttrium content was 0%.

[0060] Comparative Example 6 differs from Example 1 in that the solution temperature was not controlled during the solution treatment in this comparative example, and the actual solution temperature was adjusted to 1100℃, which is outside the solution temperature range.

[0061] The performance of the high-performance corrosion-resistant nickel-based alloy plates prepared in Examples 1-3 and Comparative Examples 1-6 was tested. The test items and test methods are as follows: Pitting potential was tested in a 3.5% NaCl solution at a temperature of 25±1℃ using a three-electrode electrochemical workstation with a scan rate of 1mV / s. The pitting breakdown potential on the anodic polarization curve was recorded. Salt spray corrosion test: In an environment of 5% NaCl solution, pH 6.5-7.2, and chamber temperature 35±2℃, the sample was continuously sprayed for 48 hours. After cleaning and drying, the mass loss per unit area was calculated. Intergranular corrosion test: Immerse the sample in a sulfuric acid-copper sulfate mixed solution at a boiling temperature of 110±1℃ for 24 hours. After bending the sample, observe the surface cracks and evaluate the grade according to the depth of intergranular corrosion. Tensile strength testing was performed using a computer-controlled electronic universal testing machine with a gauge length of 10 mm and a thickness of 2 mm. The tensile rate was 2 mm / min. The yield strength and tensile strength were recorded. High-temperature oxidation test: In an air atmosphere, in a box furnace at a temperature of 600±10℃, the sample is exposed at a constant temperature for 100 hours. After removal, the oxide scale is removed and the sample is weighed to calculate the weight gain per unit area due to oxidation.

[0062] The test data of the high-performance corrosion-resistant nickel-based alloy plates prepared in Examples 1-3 and Comparative Examples 1-6 are recorded in the table below:

[0063] By comparing and analyzing the data in the table, it can be seen that the high-performance corrosion-resistant nickel-based alloy plates prepared by the process in Examples 1-3 have superior performance compared to the nickel-based alloy plates prepared by the process in Comparative Examples 1-6. This indicates that by plasma-activating the nano-zirconia particles, a high-density hydroxyl group is obtained on their surface. This highly active surface improves the wettability of the melt to the particles in the early stage of melting and acts as an active site, inducing an interfacial chemical reaction between the particles and the matrix alloy elements. Finally, a stable transition interface layer with chemical bonds is formed between the two, realizing a strong and tough bond between the particles and the matrix, blocking the diffusion channel of the corrosive medium along the particle-matrix interface. At the same time, the rare earth element yttrium preferentially accumulates at the grain boundaries, inhibiting the precipitation of chromium carbides at the grain boundaries and improving the intergranular corrosion resistance of the alloy in a strong acid environment. The longitudinally layered carbide structure is formed by precision rolling process, which constructs a directional barrier parallel to the surface of the plate during the corrosion process, slowing down the corrosion penetration rate and achieving long-term protective stability of the alloy plate under extreme working conditions. When using a composite acid system for passivation, the specific ratio of nitric acid to chromic acid promotes an optimized balance of chromium / molybdenum atom concentration in the passivation film. Chromium oxide provides a dense passivation barrier, while molybdenum oxide imparts self-healing properties to the film, synergistically inhibiting pitting nucleation. Simultaneously, nano-titanium dioxide particles pretreated with silane are in situ embedded in the passivation film under ultrasonic oscillation. Their photocatalytic properties can decompose organic pollutants adsorbed on the film, avoiding the localized corrosion cell effect caused by dirt coverage. Through the dual upgrade of passivation film composition and structure, the alloy plate exhibits excellent resistance to pitting corrosion and fouling in chloride-containing media. In the solution treatment stage, a nitrogen-hydrogen mixed atmosphere protection and water quenching process are used in synergy. Hydrogen atoms penetrate into the alloy lattice at high temperature to inhibit carbide coarsening. Then, rapid cooling locks in the metastable supersaturated solid solution, laying the foundation for subsequent aging to control the carbide size. In the aging treatment, the forced air cooling process combined with the surface anti-oxidation coating ensures that the carbides precipitate uniformly in a specific temperature range, eliminating the tendency of micro-area galvanic corrosion caused by local stress concentration. Through the whole process of microstructure control, the alloy plate is finally endowed with comprehensive performance of resistance to uniform corrosion and stress corrosion cracking in high temperature and high pressure environment.

[0064] By comparing and analyzing the relevant data in the table, it can be seen that the nickel-based alloy plate prepared by the present invention not only has excellent pitting corrosion resistance, excellent uniform corrosion resistance, and outstanding intergranular corrosion resistance, but also shows that the nickel-based alloy plate preparation process provided by the present invention has a broader application prospect in the fields of nuclear power and marine engineering extreme corrosive environments, and is more suitable for large-scale promotion.

[0065] One of the core innovations of this invention lies in forming a longitudinally layered carbide structure through a precision rolling process, which is fundamentally different from existing rolling processes. (1) Uses ±10℃ temperature control precision to suppress abnormal grain growth; (2) Limit the deformation per pass to 30-35% to avoid dislocation concentration; (3) Control the strain rate between 0.5 and 2. The range promotes the vertical migration of carbides; (4) Implement heat preservation for ≤5s between passes to eliminate residual stress.

[0066] The synergistic effect of the above parameters has for the first time achieved continuous longitudinal arrangement of carbides with an aspect ratio of ≥5.0, forming a corrosion propagation barrier and increasing the pitting potential to ≥0.95V.

[0067] It should be noted that, in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitations, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element.

[0068] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A high-performance corrosion-resistant nickel-based alloy plate, characterized in that: The sheet material consists of the following components by weight percentage composition: Nickel: 55-65%, Chromium: 18-22%, Molybdenum: 8-12%, Iron: 2-5%, Niobium: 1-3%, Carbon: 0.05-0.15%, Yttrium: 0.05-0.2%, Nano-zirconia particles: 0.1-0.5%, the remainder being unavoidable impurities, including sulfur ≤0.01%, phosphorus ≤0.02%, oxygen ≤0.005%, and the total amount of impurities ≤0.5%; The nano-zirconia particles have a particle size of 30-80 nanometers and their surfaces are plasma-activated, resulting in a hydroxyl density of 5-8 hydroxyl groups per square nanometer on the particle surface. The microstructure of the alloy plate consists of a γ-Ni matrix phase and a dispersed C carbide composite phase. The average size of the carbides in the C carbide composite phase is ≤500 nanometers, and they are distributed in a longitudinal layered manner with an interlayer spacing of 0.5-1.5 micrometers. The plate surface is covered with a passivation film with a thickness of 50-200 nanometers and a chromium / molybdenum atomic concentration ratio of 2.0-3.

5. Titanium dioxide particles with a particle size of 20-50 nanometers are also embedded in the film.

2. A method for preparing a high-performance corrosion-resistant nickel-based alloy plate according to claim 1, characterized in that: The method includes the following steps: Step 1: Raw material preparation, weigh the raw materials according to the stated ingredient ratio; Step 2: Melting process, place the raw materials in a vacuum induction furnace and melt them under an inert atmosphere; Step 3: Casting process, pouring the molten metal into slabs; Step 4: Hot rolling treatment, the slab is heated and then rolled into shape; Step 5: Solution treatment, the rolled sheet is subjected to high-temperature solution treatment; Step Six: Aging Treatment, subjecting the solution-treated board to medium-temperature aging; Step 7: Surface passivation treatment. Immerse the aged plate in passivation solution.

3. The method for preparing a high-performance corrosion-resistant nickel-based alloy plate according to claim 2, characterized in that: In step one, the plasma activation treatment of the nano-zirconia particles includes: placing the particles in a vacuum of 1× Up to 1× In a reaction chamber at Pa, argon flow rate of 20-50 sccm and plasma power of 400-600 W, the plasma was processed for 10-20 minutes.

4. The method for preparing a high-performance corrosion-resistant nickel-based alloy plate according to claim 2, characterized in that: In step two, the melting is carried out under an argon atmosphere at a temperature of 1550-1600℃, held for 1.5-2 hours, and with a vacuum degree ≤1× Pa, and use an electromagnetic stirrer to continuously stir at 50-100 r / min.

5. The method for preparing a high-performance corrosion-resistant nickel-based alloy plate according to claim 2, characterized in that: In step three, the casting process includes: pouring molten metal into a copper mold preheated to 800-900℃, coating the surface with a 0.1-0.3mm boron nitride coating to prevent the molten metal from sticking together and to regulate the cooling rate; the pouring speed is 10-20cm / min. 3 After casting, the slab is cooled to room temperature by water at a rate of 5-10℃ / s to obtain a 50-100mm thick slab.

6. The method for preparing a high-performance corrosion-resistant nickel-based alloy plate according to claim 2, characterized in that: The hot rolling process in step four includes: The slab is held at 1100-1200℃ for 1-2 hours, and then rolled on a four-roll hot rolling mill at a pressure of 15-20MPa and a speed of 0.5-1.5m / s with a total reduction of 70-80% to obtain a longitudinal layered carbide structure with an interlayer spacing of 0.5-1.5 micrometers. Each pass requires a reduction of ≤20%, and a water mist cooling system is used to control the board temperature at 900-1000℃.

7. The method for preparing a high-performance corrosion-resistant nickel-based alloy plate according to claim 2, characterized in that: The solution treatment in step five involves a nitrogen-hydrogen mixed gas volume ratio of... : The mixture is prepared in a 95:5 ratio at a temperature of 1020-1080℃, and after holding at that temperature for 1-2 hours, it is quenched in water at a rate of ≥50℃ / s to 20-30℃ in deionized water.

8. The method for preparing a high-performance corrosion-resistant nickel-based alloy plate according to claim 2, characterized in that: The aging treatment in step six includes: holding at 700-750℃ for 4-8 hours, followed by forced air cooling at a wind speed of 5-10m / s. Before the aging treatment, the surface of the board is coated with an anti-oxidation coating for anti-oxidation protection. The coating is composed of silica sol and alumina powder in a mass ratio of 1:1, and the coating thickness is 10-20 micrometers. This prevents surface oxidation and stress corrosion during the aging treatment and ensures uniform precipitation of carbides. After the aging treatment, the surface coating is removed by mechanical grinding to provide a clean and active surface for passivation treatment.

9. The method for preparing a high-performance corrosion-resistant nickel-based alloy plate according to claim 2, characterized in that: The surface passivation process in step seven includes: The plate is immersed in a passivation solution at 40-60℃ for 30-60 minutes. The passivation solution consists of nitric acid, chromic acid and corrosion inhibitor, with a mass ratio of nitric acid:chromic acid:corrosion inhibitor = 5:3:

1. The concentration of nitric acid is 40-50wt%, the concentration of chromic acid is 20-30wt%, and benzotriazole is used as the corrosion inhibitor to achieve a Cr / Mo atomic ratio of 2.0-3.5 in the passivation film. During immersion, the ultrasonic oscillator is activated every 10-15 minutes at a frequency of 20-40 kHz and a power density of 0.5-1.0 W / cm³. 2 The oscillation time is 3-5 minutes.

10. The method for preparing a high-performance corrosion-resistant nickel-based alloy plate according to claim 9, characterized in that: The passivation solution also contains nano-titanium dioxide particles with a particle size of 20-50 nm and a total mass of 0.1-0.3%. The particles are pretreated with silane coupling agent KH-550: the particles are dispersed in ethanol, 2-5 wt% KH-550 is added, and the mixture is stirred at 60°C for 2 hours and then centrifuged and dried to allow the titanium dioxide to be uniformly embedded in the passivation film.

Citation Information

Cited By

  • Hot-corrosion-resistant nickel-based high-temperature alloy plate and preparation method thereof

    CN121759758A

  • A hot-corrosion-resistant nickel-based superalloy plate and a preparation method thereof

    CN121759758B